1999
DOI: 10.1007/s101200050069
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total gastrectomy with distal pancreatosplenectomy and D2 lymphadenectomy for advanced gastric cancer

Abstract: The standard lymph node dissection for advanced gastric cancer is a D2 dissection. Although D2 laparoscopy-assisted total gastrectomy with distal pancreatosplenectomy has been reported, no studies have reported a completely intra-abdominal laparoscopic approach, because of the technical difficulty of the procedure. We successfully performed this novel procedure in two patients with advanced gastric cancer located in the upper portion of the stomach. In fact, this surgery is technically feasible, and has a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(152 citation statements)
references
References 12 publications
0
145
0
7
Order By: Relevance
“…Consequently, several surgeons abundantly experienced in laparoscopic procedures have attempted or accomplished laparoscopic D2 lymphadenectomy during LADG and few studies had reported the possibility of applying LADG with D2 lymphadenectomy for patients with AGC [9][10][11]. Since Uyama et al first reported laparoscopyassisted total gastrectomy with D2 lymphadenectomy and distal pancreaticosplenectomy for advanced upper-third gastric cancers in 1999, there have been several studies to determine the technical feasibility of D2 lymphadenectomy in patients with AGC [4,5,[10][11][12][13][14]. However, there is no study showing the availability of LAG with D2 lymphadenectomy for treating patients with AGC in terms of surgical results such as morbidity, recurrence and survival rate, and this raises doubts about its suitability.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several surgeons abundantly experienced in laparoscopic procedures have attempted or accomplished laparoscopic D2 lymphadenectomy during LADG and few studies had reported the possibility of applying LADG with D2 lymphadenectomy for patients with AGC [9][10][11]. Since Uyama et al first reported laparoscopyassisted total gastrectomy with D2 lymphadenectomy and distal pancreaticosplenectomy for advanced upper-third gastric cancers in 1999, there have been several studies to determine the technical feasibility of D2 lymphadenectomy in patients with AGC [4,5,[10][11][12][13][14]. However, there is no study showing the availability of LAG with D2 lymphadenectomy for treating patients with AGC in terms of surgical results such as morbidity, recurrence and survival rate, and this raises doubts about its suitability.…”
Section: Discussionmentioning
confidence: 99%
“…This method was first reported by Uyama et al [17] and was modified by Wang et al [18] . Circular stapling was performed to isolate separately the esophagus and jejunum prior to anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Knotless barbed sutures (VLoc TM ; Covidien, Mansfield, MA, United States) can reduce the time of anastomosis and can ensure the safety of anastomosis, with no need for permanent traction during the whole anastomosis procedure. 9.6 ± 1.9 (7-17) 10.1 ± 2.4 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Data are mean ± SD (range). We recommend that the reconstruction method using a stapler should be selected on the basis of tumor location.…”
Section: Discussionmentioning
confidence: 99%
“…Although ten LTGs were included in this study, this was not regarded as the first report, because of its small sample size and because the results were collected by a questionnaire. Since LTG was first reported as a technical note in 1999 [26], some further studies have been reported [18][19][20][21][22][23][24]. Of these, the highest number of publications has been from Japan (n = 50), followed by Korea (n = 42; see Fig.…”
Section: Annual Publicationsmentioning
confidence: 99%